Kyiv imperial officials: publishing activities M.Grushevskiy - Nikolaichuk, D. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. The ongoing development of «hrushevoznavstvo» in the context of prosopography has provided new aspects of life and work of Hrushevskiy. The study of his personal and official relations are important for the modern Ukrainian historiography. In particular, history of his relations with imperial officials in Kiev. Purpose. The interpretation of Hrushevskiy’ publishing activity in the context of the interaction between the imperial apparatus with the censorship authorities in Ukrainian book publishing and periodical press. Results. The main official relations of Hrushevskiy with imperial administration in Kiev were determined. The study explains the specificity of provincial administration in Kiev with regard to the Ukrainian press after the declaration of the Manifesto of October 17, 1905. This research elaborates on the key means and reasons of the counteraction of imperial officials against publications of Literary and Scientific Journal, «The Village», «Sat». Originality. The novelty of the research is to try to specify Hrushevkiy’ biography, his social and political activities, organization of Ukrainian book publishing and periodical press through the position of imperial officials in relation to publishing projects of Hrushevskiy, as well as the role of the censorship authorities in it. Conclusion. The publishing activity of Hrushevsky, famous Ukrainian scientist, in Dnepr Ukraine in the early twentieth century imperial officials fairly perceived as a threat to the unity of the Russian Empire, that aims at the separation of the Ukrainian people, and therefore requires constant governmental supervision and control. Officials used various methods of direct and hidden pressure - fines, confiscation and secret circulars and orders, the main goal of which was to prevent the release of periodical press or to reduce the impact of these publications on the Ukrainian population.